Integrasi Nilai Karakter dalam Pengelolaan SDM di Perguruan Tinggi: Studi Kasus di Universitas Linggabuana PGRI Sukabumi (Lembaga Pengembangan Kinerja Dosen, 2025)
Character education is one of the essential elements that must be systematically integrated into every aspect of higher education implementation, including the management of human resources (HR), which serves as a key pillar in the execution of education. This study aims to identify and analyze how character-oriented human resource management is implemented at Universitas Linggabuana PGRI Sukabumi. The research method used is qualitative descriptive, with data collection techniques including interviews, observations, and documentation. The results of the study show that HR management strategies are carried out through value-based staff selection, character training, integration of character values into the curriculum, and performance evaluations that emphasize integrity and work ethics. This approach fosters an organizational culture that continuously supports the development of student character. The implications of these findings indicate that HR management integrated with character education can strengthen the university’s mission to produce graduates who are not only competent but also morally grounded. This research provides an important contribution to the development of value-based HR management models and serves as a reference for higher education policies focused on character formation.